The ‘Quiet Luxury’ Effect in Marketing Strategies: Between Exclusivity and Modern Consumer Appeal - Septia Sakalini Dioh; Taqwa Sultan; Margeretha Sartien Kabanga (Maneggio, 2026)
This study aims to analyze the effect of quiet luxury in modern marketing strategies, particularly the relationship between brand exclusivity and contemporary consumer appeal. The phenomenon of quiet luxury represents a shift in the meaning of luxury from conspicuous status symbols toward a more subtle, elegant, and intrinsically quality-oriented form of luxury. This research employed a descriptive qualitative approach using a library research method. Data were collected from scientific journals, academic books, industry reports, and other reliable sources related to consumer behavior, branding, and premium marketing. The data were analyzed through content analysis by classifying them into key themes, including the transformation of luxury concepts, brand differentiation, consumer perceived value, brand exclusivity, and the influence of digital media. The findings indicate that quiet luxury has become an effective marketing strategy as it enhances consumer perceived value through dimensions of quality, comfort, implicit status, and personal identity. Furthermore, this strategy strengthens brand positioning through product quality, minimalist design, limited distribution, and exclusive customer experiences. The attractiveness of quiet luxury continues to grow alongside the changing characteristics of modern consumers who are more rational, value-conscious, and sustainability-oriented. However, its implementation also faces challenges such as imitation risks, the dilemma between exclusivity and market expansion, and the demand for long-term quality consistency. This study concludes that quiet luxury is not merely an aesthetic trend, but an adaptive branding strategy highly relevant to the contemporary premium market.